1994
DOI: 10.1111/j.1464-5491.1994.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Raised Ambulatory Blood Pressure in Type 1 Diabetes with Incipient Microalbuminuria

Abstract: Whether raised blood pressure precedes, follows or develops in parallel with the onset of microalbuminuria, remains unclear. Previous studies, using conventional blood pressure recordings, have yielded discrepant results. Ambulatory blood pressure (ABP) monitoring detects borderline hypertension more reliably, and correlates more closely with end-organ damage. We have therefore compared ABP and left ventricular dimensions in normotensive insulin-dependent diabetic patients with or without microalbuminuria, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
(1 reference statement)
1
8
0
Order By: Relevance
“…We therefore believe that the rise in BP precedes persistent microalbuminuria. This is in accord with the findings of other authors who measured 24-h AMBP [7,31,63]. Studies of casual BP have suggested that microalbuminuria develops parallel to the rise in BP [64].…”
Section: Discussionsupporting
confidence: 91%
“…We therefore believe that the rise in BP precedes persistent microalbuminuria. This is in accord with the findings of other authors who measured 24-h AMBP [7,31,63]. Studies of casual BP have suggested that microalbuminuria develops parallel to the rise in BP [64].…”
Section: Discussionsupporting
confidence: 91%
“…If day‐to‐day blood pressure load over a prolonged period of time confers cardiovascular and renal risk, ambulatory blood pressure recording may theoretically be better at predicting this risk than casual clinic blood pressure recordings. Ambulatory blood pressure monitoring has previously identified variations in circadian blood pressure in both patients with essential hypertension[6–8] and diabetes mellitus[9,10] in relation to cardiac and renal outcomes. Whilst these are short‐term studies associating circadian blood pressure to changes in cardiac dimensions and renal function, there are very few long‐term outcome data available to allow an evaluation of the prognostic significance of alterations in circadian variation of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, many cross-sectional studies have been published addressing the relationship between ABPM and microalbuminuria in type 1 diabetic patients [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In 1992, Moore et al [9] studied 38 normotensive adolescent type 1 diabetic patients and found that in subjects with microalbuminuria, the nocturnal decrease was blunted but the difference did not reach statistical significance when compared with normoalbuminuric subjects.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…Studies over the last decade have shown that in type 1 diabetic patients, early kidney involvement, reflected by the presence of microalbuminuria, is often associated with an increase in blood pressure, particularly during sleep [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Do these changes in blood pressure precede increases in urinary albumin excretion (UAE) or are they concurrent?…”
Section: Introductionmentioning
confidence: 99%